Jawabanmu

2014-05-21T09:58:34+07:00
F(x) = 2x³ -(m+2)x²-(3n+2)x - 40
f(-2) = 0 ⇒ 2(-2)³ - (m+2)(-2)² - (3n+2)(-2) - 40 = 0
                   - 16 - 4m - 8 + 6n + 4 - 40 = 0
                   - 4m + 6n = 60 ......................................................(1)
f(5) = 0 ⇒ 2(5)³ - (m+2)(5)² - (3n+2)(5) - 40 = 0
                 250 - 25m - 50 - 15n - 10 - 40 = 0
                     - 25m - 15n = - 150
                       5m + 3n = 30
                       10m + 6n = 60 ..................................................(2)
Dari persamaan (2) dan (1) eliminasikan
10m + 6n = 60
 -4m + 6n = 60 -
14m = 0 maka nilai m = 0
10m + 6n = 60 ⇒ 10(0) + 6n = 60 ⇒ n = 60/6 = 10

nilai dari -3m + n = 0 + 10 = 10